Analyzing experiences of using effective feedback in the ESL classroom through the use of digital technologies - Sandí Delgado, Juan Carlos (2020)
This article of systematic literature review presents the analysis of a series of experiences that use effective feedback in educational activities through the use and integration of digital technologies, specifically, in the classes of English as a second language in higher education. The revision analyzed 14 different experiences. As part of the analysis, criteria are defined to describe and compare them, linked with the possibilities of feedback to favor the formative processes at the higher education level. Criteria include: country of origin and level of education, design of feedback used, the timing of the feedback, the means of providing feedback, and the consideration of digital technologies. The main results indicate that the use of feedback, in the ESL classroom, allows learners to boost their capacity of analysis, critical thinking, and the resolution of problems linked with interlanguage. As a conclusion, the salience and positive impact of digital technologies are highlighted in favoring the positive and effective feedback, in the particular case of English as a second language. Finally, it is evident the use of computer -mediation, screencast, and web-based learning environments as the primary sources of authors used more frequently to implement effective feedback in higher education. It concludes that the set of experiences analyzed provides light in terms of the considerations needed to design and adjust formative processes that allow boosting effective feedback mediated by digital technologies. As future work, there will be the elaboration of a methodological proposal that helps to adjust the formative processes that enable the integration of digital technologies as mediators in the process of feedback between teachers and learners.